Correlation Between Predictor Factors (Hemoglobin, Leukocytes, Platelets, LDL, HbA1c, D-dimer, Albumin) and Length of Stay in Patients with Diabetic Ulcers at Dr. Pirngadi General Hospital Medan, 2022–2023 - Hotlin Cantika Nainggolan; Bastanta Tarigan; Novrina Situmorang; Maestro Simanjuntak; Batara Simangunsong (Universitas Methodist Indonesia, 2025)
Background : Uncontrolled diabetes causes chronic complications, bothmicroangiopathies and angiopathies. Diabetic ulcers are one of thechronic complications of diabetes, caused by macroangiopathy resulting invascular insufficiency and neuropathy. Ulcers are a concern which willlead to a level of disability that will prolong the patient's treatment period.Factors that affect the length of care in diabetic ulcer patients aremetabolic control (poor blood sugar, hba1c, albumin, hemoglobin, LDL,LDL), infection control (elevated leukocytes), vascular control (increasedd-dimer coagulation). The length of treatment of diabetic ulcer patientswill burden both the patient and the state. Research: To analyze therelationship of predictor factors (hemoglobin, leukocytes, platelets, LDL,HbA1c, D-dimer, Albumin) to the length of treatment of diabetic ulcerpatients at Dr. Pirngadi Hospital Medan City. Methods: This study is ananalytic observational study with a research design using a cross-sectionalstudy. Results: Based on the results of the proportion test with the Chi-square correlation test there is a relationship between hemoglobin (p-value of 0.008), the relationship between leukocytes (p-value of 0.010), therelationship between platelets (p-value of 0.010), the relationship betweenLDL (p-value of 0.047), the relationship between HbA1C (p-value of0.046), the relationship between D-dimer (p-value of 0.025), therelationship between albumin (p-value of 0.041) with the length oftreatment of diabetic ulcer patients. In multivariate results, the factor thatmost influences the length of treatment is leukocytes. Conclusion:Hemoglobin, leukocyte, platelet, LDL, HbA1c, D-dimer, Albumin levelsare factors associated with the length of treatment of diabetic ulcerpatients at Rsud Dr. Pirngadi Medan City in 2022-2023 and leukocytesare the most influential factor.Keywords: diabetes, diabetic ulcer, length of stay